If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 2 * -1 + (-2) Multiply 2 * -1 y = -2 + (-2) y = -2 + -2 Combine like terms: -2 + -2 = -4 y = -4 Solving y = -4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -4
| 0=3 | | 60=3w^2 | | -(-2)-2=y | | -(0)-2=y | | 3x-6=4(6+3x) | | -(2)-2=y | | 2x+3y=130 | | 4.3+g=7.1 | | 2x-5=-9+39 | | 4(-2)+y=5 | | 6x+4y=240 | | c+12=39 | | 3x-6=4(5+3x) | | 4(0)+y=5 | | 12u+5=3u+50 | | 23+a=48 | | -4/7(x-10y)-1/14x | | 4(2)+y=5 | | 10=e+2.7 | | 2x+5x+8= | | 3a-7a=8 | | -3y=18-9(-2) | | 3a-7whena=8 | | -3y=18-9(0) | | 6.2*3= | | -3y=18-9(2) | | 184=23p | | 2(7)=(x+9)2/3 | | 2(-6+4x)=-84 | | 7a*3a*10B= | | y=2*0+(-2) | | 2(7)=(x+9)2 |